A pilot study of preoxygenation and apneic oxygenation with High-flow nasal cannula during RSI in emergency department : a randomized controlled clinical trial - Kijpaisalratana, Norawit; Komindr, Attasit; Musikataworn, Khrongwong (Thai Journal of Emergency Medicine, 2022)
Introduction : Desaturation is one of the most common complications during rapid sequence intubation(RSI). High flow nasal cannula has been widely studied especially in intensive care unit settings to prevent desaturation during intubation. However, the effectiveness of the treatment remains inconclusive. This is the first randomized controlled study focusing on high flow nasal cannula in patients with hypoxic respiratory failure emergency department setting. Method : This single-centered randomized controlled trial was conducted at the emergency department of King Chulalongkorn Memorial Hospital which is an urban university hospital. Acute hypoxic respiratory failure adults requiring intubation were randomly allocated to 1) standard care by RSI without apneic oxygenation, 2) preoxygenation by non-rebreathing mask with bag or bag valve mask and apneic oxygenation with nasal cannula 15LPM, and 3) preoxygenation and apneic oxygenation with 60 LPM high flow nasal cannula. Oxygenation in each patient was monitored by pulse oximetry during RSI. Objective : The primary outcome of this study was the incidence of desaturation during intubation. Result : A total of 27 patients were enrolled in this pilot study. There was no incidence of desaturation in the high flow nasal cannula group. Incidence of desaturation was demonstrated in the standard care group and nasal cannula 15 LPM group (22.2% and 28.6% respectively). However, there was no statistically significant in the proportion of desaturation patients among all study groups (28.6% standard care vs 22.2% nasal cannula 15 LPM, p=0.771; 0% high flow nasal cannula vs 22.2% nasal cannula 15 LPM, p=0.099; 0% high flow nasal cannula vs 28.6% nasal cannula, p=0.06 ) Conclusion :This study demonstrated that using a high flow nasal cannula for preoxygenation and apneic oxygenation during RSI showed no statistical significance in the incidence of desaturation comparing to the standard of care.